Analysis of Factors Causing Homosexual Behavior in Gay Teens - Reggiana Brescia; Afdal Afdal (Universitas Negeri Padang, 2021)
During the development phase, adolescents have developmental tasks that must be fulfilled. One form of adolescent development tasks is the correct sexual desire and attraction towards the opposite sex. But in reality, there are still developmental tasks that are not in accordance with norms and deviant behavior in the form of a tendency for someone with the same sex. There are many reasons that cause a person to be homosexual, for biological, psychological and environmental reasons as well as various other reasons. This study is a qualitative study aimed at analyzing the factors that cause homosexual behavior. Subjects in this study amounted to three people with criteria including the subject feeling attracted to fellow men, the subject realizes that he is attracted to the same sex, and the subject has or is in a same-sex relationship. The instruments or tools used in this study were interview and observation guidelines. To describe the factors causing gay behavior in this study, a thematic analysis was carried out by carrying out a transcript of the interview that had been verbatim. From this research, it is revealed that the factors causing gay behavior in the research subject include (1) the condition of the family background in which the relationship between the research subject and the parents has a significant influence on his decision making to be gay. The main factor found is the parenting style of parents, especially fathers, which greatly contributed to the subject's deviant and unnatural behavior, (2) the effect of the social or social environment also contributed to the subject's decision making to be gay. Therefore, it is necessary for parents to create intensive communication with their children, so that parents know and follow their children's development in order to achieve the correct sexual orientation and not deviate. The care and attention of parents towards the child's life has an important role in shaping the child's own behavior.